PENGARUH PENGAWASAN MELEKAT, MOTIVASI, DAN PEMBAGIAN KERJA TERHADAP KINERJA PEGAWAI PD BPR BKK - Sunarso, Kusmanto & (Universitas Slamet Riyadi, 2009)
ABSTRACT Target of this research is to know influence by partial and also together coherent observation, division of labor and motivation to performance officer of PD. BPR BKK Tasikmadu of Karanganyar regency and to know among variable coherent observation, motivation, or division of labor, which having an effect on dominant to performance officer of PD. BPR BKK Tasikmadu of Karanganyar regency.This research take location at PD. BPR BKK Tasikmadu of Karanganyar, regency with reason of that the office there are interesting problems relate to coherent observation, division of labor and motivation. Besides, in PD. BPR BKK Tasikmadu of Karanganyar regency available adequate data in order to supporting this research. Population in this research is all officer of PD. BPR BKK Tasikmadu of Karanganyar regency counted 143 people and as sample taken by counted 58 people with technique of proportional random sampling. Result of analysis test t indicate that coherent observation, division of labor and motivation to performance officer of PD. BPR BKK Tasikmadu of Karanganyar regency by partial. Result of F test indicate that coherent observation, division of labor and motivation have an effect on to officer performance in environment of PD. BPR BKK Tasikmadu of Karanganyar regency by together. Coefficient of determinant mean that variation of change officer performance really can be explained by variation of change coherent observation, factor motivate and division of labor equal to 88,9 and the rest 11,1% outside model. Keywords: coherent observation, motivation, division of labor and performance.